Mechanical properties and durability of textile reinforced concrete (TRC) - a review - Wu,C; Pan,Y; Yan,L (Polymers, 2023)
Textile reinforced concrete (TRC) is an innovative structure type of reinforced concrete in which the conventional steel reinforcement is replaced with fibre textile materials. The thin, cost-effective and lightweight nature enable TRC to be used to create different types of structural components for architectural and civil engineering applications. This paper presents a review of recent developments of TRC. In this review, firstly, the concept and the composition of TRC are discussed. Next, interfacial bond behaviour between fibre textile (dry and/saturated with polymer) and concrete was analysed considering the effects of polymer saturation, geometry and additives in polymer of the textile. Then, the mechanical properties (including static and dynamic properties) of TRC were reviewed. For static properties, the mechanical properties including compression, tension, flexural, shear and bond properties are discussed. For dynamic properties, the impact, seismic and cyclic properties were investigated. Furthermore, the durability of TRC under different environmental conditions, i.e., temperature/fire, humidity and wet–dry cycles, freeze–thaw, chemical and fatigue were discussed. Finally, typical engineering applications of TRC were presented. The research gaps which need to be addressed in the future for TRC research were identified as well. This review aims to present the recent advancement of TRC and inspire future research of this advanced material.